When should DIY have a localized healthcare waste management system? - Hasanbasri, Mubasysyir; Sarto; Wiranto; Sutena, Marthinus; Qaimamunazzala, Hayu; Ferdiana, Astri; Ramadona, Aditya Lia; Jaladara, Vena; Nilasari; Meliala, Andreasta; Padmawati, Retna Siwi (BKM Public Health and Community Medicine, 2023)
Purpose: The 2018 healthcare waste management crisis catalyzed a critical review of the concerns expressed by the Health Office (dinkes) and healthcare facilities regarding healthcare waste management in the Special Region of Yogyakarta (DIY). Due to this crisis, the Ministry of Health hired Universitas Gadjah Mada (UGM) to look into potential solutions and promote DIY government policy responses. This paper examines the management strategy during crisis times and possible alternative solutions. Methods: This paper uses focused group discussions reports involving separate groups of (1) environmental health officials from community health centers, (2) hospitals, (3) environment health officials of district health authorities, and (4) cross-sectoral province officials in the Yogyakarta Special Region. It is part of a project 'A case study of strengthening regional-based medical waste management model', fund from the Environmental Health Directorate, Directorate General of Public Health, Ministry of Health (Project KN 01.03/6.1/0198/2019). Result: A simulation of policy options based on health facility managers suggests that a province-based system is the most profitable in the long term for DIY, with several possible options. The national policy roadmap was considered inadequate to respond to DIY's urgent local needs. Furthermore, the series of meetings succeeded in forming an informal forum between health facilities, provincial health offices, and associations of hospital environmental sanitation experts, monitoring medical waste management. Conclusion: The 2018 medical waste management crisis led to the formulation of policy response choices tailored to the capacity of DIY. These choices considered the expenditures and legal sanctions faced by healthcare facilities and the economic value of a region-based waste system for local government authorities. This comprehensive approach highlights the importance of local capacity. It needs to shape effective and sustainable medical waste management policies, underscoring the necessity of region-specific strategies in the face of national health crises.